Morphological and physiological predictors for selection at national and league status for youth soccer players - Kalata, M.; Williams, C. A.; Varjan, M.; Bujnovsky, D.; Zahalka, F.; Maly, T. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Identifying talent with relevant physical predictors to establish players at the elite level has always been topical for soccer and sport science departments. But due to the large number of factors responsible for performance, there is still no consensus for the selection of key objective tests. However, the professionalisation of youth soccer has resulted in increased physical requirements of the players. Therefore, the aim of the study was to examine physical predictors to differentiate players who have reached the highest level (national team) of youth elite soccer compared to non-selected peers.